Pendampingan Regenerasi Penderes Nira Aren Desa Kayupuring Kecamatan Petungkriyono - Hendri Hermawan Adinugraha; Muhammad Khoirul Fikri; Sukirno Sukirno (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
This service aims to analyze the regeneration conditions of palm juice penderes which are used as palm sugar. The youth population as the regeneration of palm sugar growers in Kayupuring village is the spearhead of sustainable palm sugar production. The interest of the community, especially the youth, in the production of palm sugar is very small. They prefer to work in other fields other than as a palm juicer. This community service was conducted in the village of Kayupuring, Petungkriyono District, Pekalongan Regency in March 2020. The data collection methods in this study were interviews, documentation, observation and data validity methods using the triangulation method of data sources which included sugar palm growers (producers), youth, and the government. Kayupuring village. The results of the study concluded that the condition of the regeneration of palm sugar palm growers in Kayupuring village was worrying. The lack of youth and youth awareness is the root of the problem in the regeneration of palm sugar palm growers in Kayupuring village. The role of youth is very important for the sustainability of palm sugar in Kayupuring village. However, the participation of the village government as the holder of the government needs to be carried out as a supporter so that youth awareness will grow and the regeneration of palm juice growers will be maintained. Supporting efforts in making youth aware are by holding workshops or socialization as well as trainings on more modern palm sap management as a form of empowerment to the community. Village funds are allocated for community empowerment so that the benefits of village funds can be felt in the long term.